english: english - Mahmudyah, Arida; Habibie, Rudy (Faculty of Law, University of Mataram, 2023)
Project problems in tender competitor auctions often occur due to several issues, one of which is the teamwork in the Raha-Tampo Shaft Road Improvement Project Package (EIB-I07) at Muna Island, Muna Regency, Southern Sulawesi. Breaking promises, whether intentional or unintentional, by a party. When a party does not experience justice in the implementation of the engagement and desires to change some of the agreement content, they can deliver a letter in the form of an addendum. The content of an addendum often contradicts the main agreement made in front of the notary. The aims of this writing are to discover and analyze the legitimacy of addendums made by parties under the hands due to the occurrence of broken promises in the certificate of cooperation agreement, and to discover and analyze the legal considerations made by the judge in determining the case 51/Pdt.Plw/2016/PN.Kdi. This research utilized the normative juridical approach, which is a method that relies on secondary data as the primary source of information. The secondary data is obtained through library research, specifically by reviewing legal regulations, documents, or books related to the researched topic. The result of this study mentions that, basically, an addendum can be added to an agreement as long as all parties agree. This is because adding an addendum allows for the addition, modification, or removal of a specific issue in the agreement, which is always related to the principal agreement. This is regulated in Article 1320 of the Civil Code, which concerns the conditions for an agreement to be valid. The agreement is valid because there is a mutual agreement among all parties involved, the parties have the ability to enter into a contract, and the subject matter of the agreement is legal. The main key of an addendum is the agreement between all parties, in accordance with Article 1320 of the Civil Code.